Project-Based Entrepreneurship Learning to Foster Entrepreneurial Spirit - Pajala, Semuel; Aprizal, Aprizal; Ferawati, Andi; Azis, Abd.; Rauf, Rusdiaman (Fakultas Ekonomi, Universitas Muslim Indonesia, 2025)
This study aims to examine the implementation of Project-Based Learning (PjBL) in Entrepreneurship Education at Universitas Handayani Makassar, using a qualitative approach that combines literature review and in-depth interviews with six lecturers who have applied PjBL in entrepreneurship teaching. The findings from the interviews indicate that PjBL effectively increases student engagement in learning, enriches their practical experiences, and develops essential skills such as problem-solving, communication, and collaboration. However, challenges faced in its implementation include time constraints, limited resources, and the lecturers' readiness to provide intensive guidance to students. Additionally, the role of lecturers as facilitators is crucial to the success of the PjBL model. Based on the research findings, it is recommended that the institution provide additional training for lecturers, enhance the curriculum to integrate PBL better, and offer facilities to support project-based learning. The implementation of PjBL is expected to improve the quality of entrepreneurship education and better equip students with the necessary skills to navigate the competitive business world.